2018
DOI: 10.1021/acs.jpclett.8b00572
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Dimensional Cesium Lead Halides: History, Properties, and Challenges

Abstract: Over the past decade, lead halide perovskites (LHPs) have emerged as new promising materials in the fields of photovoltaics and light emission due to their facile syntheses and exciting optical properties. The enthusiasm generated by LHPs has inspired research in perovskite-related materials, including the so-called “zero-dimensional cesium lead halides”, which will be the focus of this Perspective. The structure of these materials is formed of disconnected lead halide octahedra that are stabilized by cesium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
247
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(265 citation statements)
references
References 117 publications
(461 reference statements)
11
247
1
Order By: Relevance
“…Within the Cs 4 PbBr 6 NCs, the [PbBr 6 ] 4− octahedra are completely decoupled in all dimensions as a result of minimal electronic overlap between the adjacent octahedra. Therefore, the 0D perovskite NC system always exhibits a molecular-like absorption, and the size of the NCs does not have any remarkable effect on the band structure, which is consistent with the report by Manna 8,18 . Meanwhile, this unique structure renders a strong quantum confinement to confine charge carriers inside the octahedra to easily form bound excitons, which is exemplified by the clear and sharp excitonic peak in the absorption spectrum of this material without applied pressure, as shown in Supplementary Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Within the Cs 4 PbBr 6 NCs, the [PbBr 6 ] 4− octahedra are completely decoupled in all dimensions as a result of minimal electronic overlap between the adjacent octahedra. Therefore, the 0D perovskite NC system always exhibits a molecular-like absorption, and the size of the NCs does not have any remarkable effect on the band structure, which is consistent with the report by Manna 8,18 . Meanwhile, this unique structure renders a strong quantum confinement to confine charge carriers inside the octahedra to easily form bound excitons, which is exemplified by the clear and sharp excitonic peak in the absorption spectrum of this material without applied pressure, as shown in Supplementary Fig.…”
Section: Resultssupporting
confidence: 91%
“…Although some works showed that Cs 4 PbBr 6 NCs or the bulk structure possess fluorescence in the visible region 2224 , an ongoing debate about the origin of the emission for these systems remains. The recent report by Manna et al 8,18 proposed a more reasonable explanation, deepening the insight into the nonfluorescent mechanism of the Cs 4 PbBr 6 systems. According to their reports 8,18 , the origin of PL can be attributed to the presence of 3D perovskite impurities embedded inside the Cs 4 PbBr 6 matrix, rather than to the intrinsic emission of Cs 4 PbBr 6 .
Fig.
…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Controversial results on the physical properties of Cs 4 PbBr 6 have been reported recently, with some claiming that it has intrinsic green emission, and others believing it is non-emissive in the visible wavelength. A recent perspective by Manna et al has provided detailed discusses on the contrasting opinions on the properties, and suggested that defect-free Cs 4 PbBr 6 has an intrinsic large band gap of > 3.2 eV and the green emission of those Cs 4 PbBr 6 materials is likely from contamination by CsPbBr 3 nanocrystal-like impurities [131]. To our point of view, Cs 4 PbBr 6 cannot be considered as 'true' 0D structure, because the Cs + cations are too small to have individual metal halide octahedra completely isolated from each other without electronic band formation.…”
Section: D Metal Halide Hybridsmentioning
confidence: 99%
“…Therefore, it is more reasonable to deduce that nanosized CsPbBr 3 NCs were formed regardless of the fabrication techniques of Cs 4 PbBr 6 micro or macro crystals. [120] Very recently, we developed a HBr-assisted slow cooling method to fabricate Cs 4 PbBr 6 single crystallites with embedded CsPbBr 3 NCs. [121] as depicted in Figure 8a,b.…”
Section: In Situ Fabricated Pncs Embedded In Crystalline Matrixmentioning
confidence: 99%